Pengawasan Mutu Produk Susu Pasteurisasi Kemasan Cup Di Milk Treatment Koperasi(Quality Control of Pasteurized Milk Product on CupPackaging in Milk Treatment of Koperasi PeternakanBandung Selatan (MT-KPBS) Pangalengan Bandung - Migie Handayani; Slamet Hartono (Agro Ekonomi, 2003)
The study was conducted to identify the implementation of supervision on the pasteurized milk product quality and to explore the result of supervision on the cup packaged chocolate and strawberry flavor milk quality. The method utilized in this research was descriptive method. Data analyzed was time series, one obtained from MT-KPBS Pangalengan Bandung. Analysis method exploited were p-chart and multiple linear regression method. Result indicated that fresh milk collected at MT-KPBS Pangalengan Bandung contained higher fat content compared with standard quality condition that MT-KPBS stated. Quality supervision that MT-KPB implemented involved supervisions on raw material quality and product quality. Pasteurization milk was bad and defects with both chocolate and strawberry flavor were located between upper controlled limit (UCL) and lower controlled limit (LCL). This indicated that the defect occurred is still at under control limit. Laboratory and packaging personnel are not significantly affected to the defect of chocolate and strawberry flavor pasteurizedmilk